Field notes contributed by James J. Dinsmore, fall 1977 - Dinsmore, James J.et al (1977)
Field notes contributed by James J. Dinsmore with observers Richard Sojda, Gene Burns, Gladys Black and others . This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of fall 1977. Epson - sheet feed/flatbed